2020
DOI: 10.3389/fnagi.2020.587989
|View full text |Cite
|
Sign up to set email alerts
|

Differential Profile of Systemic Extracellular Vesicles From Sporadic and Familial Alzheimer’s Disease Leads to Neuroglial and Endothelial Cell Degeneration

Abstract: Evidence suggests that extracellular vesicles (EVs) act as mediators and biomarkers of neurodegenerative diseases. Two distinct forms of Alzheimer disease (AD) are known: a late-onset sporadic form (SAD) and an early-onset familial form (FAD). Recently, neurovascular dysfunction and altered systemic immunological components have been linked to AD neurodegeneration. Therefore, we characterized systemic-EVs from postmortem SAD and FAD patients and evaluated their effects on neuroglial and endothelial cells. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 109 publications
(136 reference statements)
1
22
0
Order By: Relevance
“…Although we did not observe changes between dementia cases by immunoprecipitation, it was clear by confocal microscopy that BACE1 was overregulated mainly in astrocytes on FAD and SAD groups, with a particular association with vessels in SAD. Additionally accumulated CLDN5 was found according to previous reports (Villar-Vesga et al, 2020;González-Molina et al, 2021). Such BACE1 + reactive astrocytes associated to disrupted vessels were also closer but not overlapping with PHF-tau.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although we did not observe changes between dementia cases by immunoprecipitation, it was clear by confocal microscopy that BACE1 was overregulated mainly in astrocytes on FAD and SAD groups, with a particular association with vessels in SAD. Additionally accumulated CLDN5 was found according to previous reports (Villar-Vesga et al, 2020;González-Molina et al, 2021). Such BACE1 + reactive astrocytes associated to disrupted vessels were also closer but not overlapping with PHF-tau.…”
Section: Discussionsupporting
confidence: 76%
“…Complementarily to these data, we have found differential patterns of astrocytes implication in dementia using additional markers such as AQP4, GS1, GLAST1, and for ECs such as Lectin UEA, vimentin, PECAM1 and CLDN5. However, SAD always showed more affection in relationship with disrupted vessels, less thickness, and more production of CLDN5 + extracellular vesicles (EVs) [Henao-Restrepo J et al data non published ( Villar-Vesga et al, 2020 ; González-Molina et al, 2021 )]. Furthermore, the study from Gonzalez-Molina et al suggested that EVs from astrocytes of 3xTgAD mice and AD human brain carried out messages that produced endothelial disruption and neuronal retraction ( González-Molina et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the difference between young or normal BBB and aged or dysfunctional BBB. (Bell and Zlokovic, 2009;Grinberg and Thal, 2010;Richardson et al, 2012;Rouhl et al, 2012;Sagare et al, 2012) Yes (Salmina et al, 2010;Villar-Vesga et al, 2020;Chacón-Quintero et al, 2021;González-Molina et al, 2021) Yes (Wardlaw et al, 2003;Zhang et al, 2014;Rajani et al, 2018;Wang et al, 2018;Tayler et al, 2021;Zhu et al, 2021) Extracellular components…”
Section: Phenotypes Of Bbb Breakdown In Normal Agingmentioning
confidence: 99%
“…treatment to halt the progression of AD and no systemic biomarkers for early diagnosis of AD (Villar-Vesga et al, 2020). Early detection and intervention of AD is key in prevention, lowering the economic burden, and improving patient quality of life.…”
mentioning
confidence: 99%